Antigone's ghosts : the long legacy of war and genocide in five countries - Wolfgram, Mark, 1970- (Bucknell University Press, 2019)
"Sophocles' play Antigone is a starting point for understanding the perpetual problems of human societies, families, and individuals, who are caught up in the terrible aftermath of mass violence. What is one to do after the killing has stopped? What can be done to try and prevent a round of new violence? The tragic and dramatic tension in the play is put in motion by setting an unyielding Antigone against King Creon. As we see through the investigation of how Germany, Japan, Spain, Yugoslavia and Turkey have dealt with their histories of mass violence and genocide in the 20th century, the forces represented by Antigone and Creon remain very much part of our world today. Through a comparison of the five countries and their political institutions (democratic and authoritarian) and cultural traditions (Western and non-Western), we begin to appreciate the different pathways that societies have taken when confronting their violent histories"--